Ideal Cardiovascular Health in the southern cone of Latin America. (March 2018) - Seron, P.; Irazola, V.; Rubinstein, A.; Calandrelli, M.; Ponzo, J.; Olivera, H.; Gutierrez, L.; Elorriaga, N.; Poggio, R.; Lanas, F.
Abstract: Objective: The American Heart Association developed the concept of 'Ideal Cardiovascular Health', which is based on the presence of ideal levels across seven health factors. The goal of this study is to assess the prevalence of Ideal Cardiovascular Health in the Southern Cone of Latin America. Study design: We conducted a cross-sectional analysis as part of CESCAS I cohort. Methods: This report included 5458 participants aged between 35 and 75 years who were selected using stratified multistage probability sampling in Argentina, Chile and Uruguay. Interviews included demographic information, the International Physical Activity Questionnaire, and a food frequency questionnaire on dietary habits. Participants were classified as current, former or non-smokers. Weight, height and blood pressure were measured by trained personnel, and fasting cholesterol and glucose plasma levels were measured. Results: Only 0.1% (95% confidence interval [CI]: 0.0–0.2) met the seven criteria that define the Ideal Cardiovascular Health. The least prevalent healthy behaviour was having a healthy diet: 0.5% (95% CI: 0.3–0.7), while the least prevalent health factor was having blood pressure < 120/80 mmHg: 23.6% (95% CI: 22.1–25.0). Conclusions: The prevalence of Ideal Cardiovascular Health is very low in a representative sample of population from the Southern Cone of Latin America, and the levels of healthy lifestyle behaviours are even lower than ideal biochemical parameters. These results highlight the challenge of developing strategies to improve the levels of Ideal Cardiovascular Health at primary prevention levels. Highlights: Ideal Cardiovascular Health includes seven favourable cardiovascular behaviours and health factors. Behaviours include smoking, body mass index, physical activity and diet. Health factors include total cholesterol, blood pressure and glycaemia. Only one from 5458 participants from Southern Cone of Latin America accomplished all seven criteria.